SOSIALISASI PERENCANAAN PAJAK DI DESA KOTA PARI KECAMATAN PANTAI CERMIN - Adiman, Sumardi; Rizkina, Miftha; Aliah, Nur; Maharani, Juana Dewi (LPPM Institut Teknologi dan Bisnis Kristen Bukit Pengarapan, 2024)
The aim of carrying out this service is the downstreaming of the research plan carried out to provide understanding to SMEs in accounting and investing as well as creating and developing understanding so that they have an awareness of investing from an early age. Understanding financial planning will have a big impact on business development and in the future. Method used starting from identifying problems, designing activity programs, socializing tax planning in managing business finances properly and correctly, activities in this Community Partnership Program are carried out in an integrated manner. offline. The learning method and approach applied in achieving basic competency in this activity is a participatory method, where the material delivery pattern is based on the golden rule. Village officials responded enthusiastically to this Community Partnership Program, as evidenced by the large number of village officials and communities participating and discussing. This Community Partnership Program has succeeded in increasing the understanding and capabilities of village officials in Kota Pari Village.